PERENCANAAN DINAMIK MELALUI TRAINING NEEDS ASSESSMENT(TNA) - HM Sukardi HM Sukardi (LPMPP Universitas Negeri Yogyakarta, 2001)
l'h0Ug/1 regional autonomy was alread.y declared to start being in effect inJanuary 2001, lteads o.t·governntent offices and the public in getleral in ntany provinces andregencies are still Izesitanf in putting tlze pO/icy into practice.The obJ'ective ( f tIle discussion in tlzis article on dynamic planning througlfTraining Need A ssessntent(rNA) is I() provide the basis (if (Jperati()nal rationale and actualsteps related to planning oriented to tIle need,; ( fsociety, which has seldom been done alltltis til1te·as a consequence oj'overly centrally dOllzinated aut/torily causil'zg /fead officials ofregional inJstitutions to junetion only as good execut()rs ofpolicies.The process ofplanning a INA-oriented institution oj'education and training goestltroug/l seven intportant steps: (a) .forlning a planning team tltat work well togel/fer andrepresent bottom, middle, and top layer Ilead o.fficia/s, (b) making ..ũrveys on the trends andissues related to tile per.formance tllat will become tlte target oj improvement, (c) cJloosingtlte approacll to he used to determine the direction (if tlte rNA planning, (d) designing ordeveloping instruments 111at will effiCiently elicit if1:formation from users or customers, (e)distributing the instrulnents to the users, administratively processing tltose tltat return, andanaly=ing tJleln on tIle basis ()j' users' responses, (f) interpreting, assessing, and ranking tomake, decisions on needs' priority, and (g) submit the priorities of needs as the basicmaterials in planning tile institutiOl1 's programs.Tllroug/l tlze step,, · above, tlze planning of education and training is Il0ped topossess cltaracteristics tlzat support tile acJlievelnenf o.fthe programs ' ffectiveness.